2021
DOI: 10.1016/j.ygyno.2021.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Results of TRIO-14, a phase II, multicenter, randomized, placebo-controlled trial of carboplatin-paclitaxel versus carboplatin-paclitaxel-ganitumab in newly diagnosed epithelial ovarian cancer

Abstract: Addition of ganitumab to carboplatin paclitaxel chemotherapy in primary EOC did not improve progression-free survival.• Neutropenia, thrombocytopenia and hyperglycemia were more common in the ganitumab group when compared to the placebo group.• Patients with low expression of tumor IGFBP2 may have increased IGF bioavailability and may benefit from ganitumab.• Our results do not support further study of ganitumab in unselected EOC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The drug candidates targeting IGF-1R signaling that are under clinical trial investigation include: IGF ligand inhibitors, which are monoclonal antibodies targeting IGF-1/2; IGF-1R antagonists, which encompass some antibodies and kinase inhibitors; as well as insulin receptor substrate 1 (IRS-1) inhibitors, PI3K inhibitors, and mTOR inhibitors alone or in combination ( 25 , 52 , 64 , 65 ). These agents are of the same classes of drugs abandoned due to their high toxicity ( 41 , 53 ).…”
Section: Challenges For Clinical Use Of Igf-1r-silencing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug candidates targeting IGF-1R signaling that are under clinical trial investigation include: IGF ligand inhibitors, which are monoclonal antibodies targeting IGF-1/2; IGF-1R antagonists, which encompass some antibodies and kinase inhibitors; as well as insulin receptor substrate 1 (IRS-1) inhibitors, PI3K inhibitors, and mTOR inhibitors alone or in combination ( 25 , 52 , 64 , 65 ). These agents are of the same classes of drugs abandoned due to their high toxicity ( 41 , 53 ).…”
Section: Challenges For Clinical Use Of Igf-1r-silencing Agentsmentioning
confidence: 99%
“…Plausible explanations for incongruence of findings on the role of IGF-1R include the complex compensatory mechanisms mediated by other tyrosine kinase receptor pathways and interspecies differences. For instance, the addition of ganitumab, a monoclonal antibody targeting IGF-1R, to carboplatin/paclitaxel chemotherapy in patients with primary epithelial ovarian cancer did not improve progression-free survival in a phase II multicenter controlled trial ( 65 ), despite the promising results of IGF-1R inhibition in various preclinical studies ( 25 , 32 , 64 ). In addition, although both receptors facilitate chemoresistance to the selective estrogen receptor modulator (SERM) tamoxifen in breast cancer, resistance to tamoxifen is characterized by decreased expression of IGF-1R and increased EGFR expression, and more surprisingly, no detectable difference was found in EGFR expression between breast cancer cells resistant and sensitive to tamoxifen when measured with cytometry ( 79 ).…”
Section: Challenges For Clinical Use Of Igf-1r-silencing Agentsmentioning
confidence: 99%
“…Understanding the importance of IGF-1R signaling has prompted the development and clinical evaluation of several potential anticancer therapeutics, targeting signaling through the IGF axis [ 9 ]. These drug candidates are, for example, monoclonal antibodies, directly interacting with IGF-1R, and they include ganitumab [ 10 , 11 , 12 ], figitumumab [ 13 , 14 ], cixutumumab [ 15 , 16 ], and dalotuzumab [ 17 , 18 ]. The results from clinical trials including these mAbs has unfortunately only shown a modest clinical benefit for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical trials were performed on unselected patient groups, and a more prominent response was found for a subset of the ovarian [ 10 ], pancreatic [ 19 ], and prostate [ 20 ] cancer patients. Moreover, the combination of the standard regimen with such antibodies was sometimes associated with an increased rate of adverse effects [ 11 , 13 ]. It has therefore been suggested that a subset of patients might benefit from IGF-1R-targeted therapy on the precondition of identification of the appropriate predictive biomarkers [ 11 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation